Results of Microbiological Study of Sterility of Domestic Osteoplastic Material "OSS.UZ" (Texas Journal of Medical Science, 2022)
Air is one of the most significant factors of microbial pollution. Usually, mechanical particles that pollute the air are carriers of microflora. The results of microbiological study of osteoplastic material after radiation exposure are considered equal. Prior to sterilization, the osteoplastic material was packaged. Research has revealed the best dosage of radiation to sterilize both components Oss.uz